Alteration of Hepatic Function: Helpful to Diagnose and Assess Severity of Perinatal Asphyxia (Bangladesh Journal of Child Health, 2010)
Background and Objectives: Diagnosis of perinatal asphyxia is mostly establishedretrospectively. But it is difficult to diagnose perinatal asphyxia retrospectively in theabsence of perinatal records. As because of hypoxaemia, different organ systems ofthe body are affected in perinatal asphyxia, this study was done to assess the hepaticfunction for the diagnosis of perinatal asphyxia and to find out any correlation existingbetween hepatic enzyme change and the severity of perinatal asphyxia.Methods: A total of 70 full-term asphyxiated newborns (study group) were studiedduring January 2008 to December 2008 in the department of Paediatrics, MymensinghMedical College Hospital. After enrolment these babies were grouped according toSarnat and Sarnat stages of HIE as stage I, II and III. Another 50 healthy newbornswere also studied as reference group. Venous blood was analyzed between 2nd and5th day of life to estimate serum AST, ALT and alkaline phosphatase (ALP), serumtotal bilirubin (STB), serum total protein (STP), serum albumin and prothrombin time(PT). Unpaired student’s 't' test and Spearman's rank correlation was used for dataanalysis and P value of